Comparison of Norepinephrine and Phenylephrine Infusions for Maintenance of Haemodynamics Following Subarachnoid Block in Lower Segment Caesarean Section - Areeb, Muhammad; Hussain, Tanvir; Mushtaq, Sadaf; Ali, Saqib; Imran, Faisal; Siddiqui, Shamila Athar (Biological and Clinical Sciences Research Journal, 2025)
Phenylephrine (PE) is widely regarded as the drug of choice for treating maternal hypotension during cesarean delivery under subarachnoid block. However, growing evidence from recent studies indicates that norepinephrine (NE) is an effective alternative. Objective: To compare the outcome of norepinephrine and phenylephrine infusions for maintenance of hemodynamics following subarachnoid block in lower segment caesarean section. Methods: This randomized controlled trial took place at the Department of Anesthesiology, National Hospital and Medical Centre, Lahore, from 1st July 2024 to 1st January 2025, enrolling 84 patients undergoing cesarean section under subarachnoid block. Patients were randomly assigned to receive PE or NE infusions, and intraoperative bradycardia (HR <50 bpm) was recorded. Statistical analysis was carried out using the Mann-Whitney U test for continuous variables and the Chi-square or Fisher's exact test for categorical variables, with p ≤ 0.05 considered significant. Stratification for potential confounders was also performed. Results: Baseline demographics were comparable between groups (p > 0.05 each). The incidence of bradycardia was substantially higher with PE (61.9%) compared to NE (9.5%) (p = 0.000). Stratified analyses confirmed lower bradycardia rates with NE across age groups (7.7% vs. 63.6%, p = 0.000; 12.5% vs. 60.0%, p = 0.004), parity groups (8.3% vs. 56.7%, p = 0.000; 16.7% vs. 75.0%, p = 0.019), ASA II patients (9.5% vs. 61.9%, p = 0.000), and term gestations (9.5% vs. 65.0%, p = 0.000). Conclusion: Norepinephrine is a favorable alternative to phenylephrine for preserving maternal blood pressure during subarachnoid block for cesarean delivery. Given its lower incidence of bradycardia across all subgroups, norepinephrine can be considered the preferred vasopressor for routine clinical use in obstetric anesthesia.